Peran Negara dalam Memenuhi Hak Pendidikan dalam Mewujudkan Sustainable Development Goals (SGDs) Pendidikan Berkualitas dan Kesetaraan Gender - Theresia Maya Burak Hurint; Winsherly Tan; Winda Fitri (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study analyzes the role of the state in fulfilling gender-equal educational rights in Indonesia within the framework of the Sustainable Development Goals (SDGs), particularly the goals of quality education and gender equality. This research employs a normative juridical approach by examining statutory regulations, education policies and supporting empirical data related to educational access and protection. The novelty of this study lies in its analysis of the gap between formal legal guarantees and the achievement of substantive gender justice in education. The findings show that Indonesia has established an adequate legal foundation to guarantee the right to education without discrimination; however, its implementation remains ineffective in several aspects. Disparities are still evident in access to higher education, women’s participation in STEM fields, protection from gender-based violence in educational settings and educational accessibility for women in remote areas and vulnerable groups. The main barriers are not limited to regulatory issues but also include patriarchal culture, geographical inequality, economic constraints, limited gender-responsive curricula and weak institutional capacity. This study emphasizes that fulfilling gender-equal educational rights requires stronger legal enforcement, affirmative policies, preventive and repressive protection mechanisms and sustained social transformation to achieve the SDGs in a more inclusive and substantive manner